2013
DOI: 10.1016/j.brs.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation Elicits Rate-Dependent Brain Network Responses in Non-Human Primates

Abstract: Background Transcranial magnetic stimulation (TMS) has the potential to treat brain disorders by tonically modulating firing patterns in disease-specific neural circuits. The selection of treatment parameters for clinical repetitive transcranial magnetic stimulation (rTMS) trials has not been rule-based, likely contributing to the variability of observed outcomes. Objective To utilize our newly developed baboon (Papio hamadryas anubis) model of rTMS during position-emission tomography (PET) to quantify the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 73 publications
2
25
0
Order By: Relevance
“…Cerebral blood flow was measured during 3 Hz, 5 Hz, 10 Hz, and 15 Hz TMS applied to M1. The data demonstrated that the CBF response was optimal at 5 Hz rTMS not only at the site of stimulation, but also in the connected motor areas (Salinas et al, 2013). In addition, we found no significant CBF changes at any rTMS frequency in the homologous contralateral M1 hand region.…”
Section: Discussionmentioning
confidence: 98%
“…Cerebral blood flow was measured during 3 Hz, 5 Hz, 10 Hz, and 15 Hz TMS applied to M1. The data demonstrated that the CBF response was optimal at 5 Hz rTMS not only at the site of stimulation, but also in the connected motor areas (Salinas et al, 2013). In addition, we found no significant CBF changes at any rTMS frequency in the homologous contralateral M1 hand region.…”
Section: Discussionmentioning
confidence: 98%
“…> 1 Hz) will produce excitatory brain activity in all nodes of the targeted brain network. In this study, we extend our previous results 8,9 by investigating the effective connectivity of the baboon’s motor network—at different rTMS frequencies—to determine if 5 Hz rTMS is the optimal frequency for stimulation of all of the nodes within the motor network.…”
Section: Introductionmentioning
confidence: 60%
“…11 The data acquired in these five animals was used in prior publications 8,9 ; the results from these prior publications were reanalyzed in this study to assess the effective connectivity of the baboon’s motor network. Each animal was pre-screened—using electroencephalography 12 —to ensure that only animals with no neurological deficits were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations